2013
DOI: 10.1093/nar/gkt735
|View full text |Cite
|
Sign up to set email alerts
|

One antitoxin—two functions: SR4 controls toxin mRNA decay and translation

Abstract: Type I toxin–antitoxin systems encoded on bacterial chromosomes became the focus of research during the past years. However, little is known in terms of structural requirements, kinetics of interaction with their targets and regulatory mechanisms of the antitoxin RNAs. Here, we present a combined in vitro and in vivo analysis of the bsrG/SR4 type I toxin–antitoxin system from Bacillus subtilis. The secondary structures of SR4 and bsrG mRNA and of the SR4/bsrG RNA complex were determined, apparent binding rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 43 publications
1
84
0
2
Order By: Relevance
“…An exception is the bifunctional antitoxin SR4 that does not only promote bsrG RNA degradation but also impedes translation by inducing a conformational change around the toxin RBS. 23 However, neither SR5 nor RatA binding alters the structure of the cognate toxin RBS. 25,22 Therefore, we can conclude that SR5 does solely promote Figure 8.…”
Section: Discussion Bsre/sr5 Is a Type I Ta Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…An exception is the bifunctional antitoxin SR4 that does not only promote bsrG RNA degradation but also impedes translation by inducing a conformational change around the toxin RBS. 23 However, neither SR5 nor RatA binding alters the structure of the cognate toxin RBS. 25,22 Therefore, we can conclude that SR5 does solely promote Figure 8.…”
Section: Discussion Bsre/sr5 Is a Type I Ta Systemmentioning
confidence: 99%
“…In B. subtilis, 14 type I TA systems were proposed, 21 and 5 of them are located on prophage regions. Of those, txpA/RatA, 8,22 and bsrG/SR4 11,23,24 have been investigated in some detail. bsrG/SR4 is the first temperature sensitive type I TA system, as bsrG RNA is rapidly degraded at 48 C. SR4 is a bifunctional antitoxin that promotes bsrG RNA degradation by recruiting RNase III, and additionally induces a structural change around the bsrG RBS that further obstructs translation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction promotes degradation of the bsrG mRNA through cleavage of the duplex by RNase III and subsequent degradation of the remaining RNAs by endonuclease Y and the 3=-to-5= exoribonuclease R (112). However, RNase III is not essential for the functioning of the toxin-antitoxin system (113), and this might be due to a second role of SR4 in inhibiting bsrG mRNA translation (114). As for the txpA-ratA module, it was suggested that the function of the bsrG-SR4 module is to prevent excision of the SP␤ prophage element from the B. subtilis genome.…”
Section: Independently Expressed Small Rnas and Rna Antitoxinsmentioning
confidence: 99%
“…The deletion of sr4 or overexpression of bsrG causes cell lysis on agar plates. SR4 is a bifunctional antitoxin, as it promotes toxin mRNA degradation by an RNase III-dependent mechanism (Jahn et al, 2012) and, additionally, induces a conformational alteration around the bsrG SD sequence impeding ribosome binding (Jahn & Brantl, 2013). Recently, we have shown that the toxin BsrG is recruited to the cell membrane, but surprisingly neither induces pore formation nor causes energy starvation.…”
Section: Introductionmentioning
confidence: 99%